The Influence Of The Project Based Learning (PJBL) Learning Model On Student Learning OutComes In PPKN Subject - Sati Sati; Aiman Faiz; Lestari Lestari (Universitas Pendidikan Indonesia, 2024)
This research is motivated by the learning process which is still conventional. This research aims to determine student learning outcomes by implementing the Project Based Learning (PjBL) learning model in PPKn subjects in class V. This research approach uses a quantitative research type, Pre-experimental research design with a One Group Pre test-Post test design. Design. This research uses documentation study instruments, learning outcomes tests. Hypothesis testing using paired sample t-Test. The results of the hypothesis test on learning outcomes obtained a value of sig = 0.000. This means, the results of hypothesis testing on learning outcomes, pretest data, posttest data have a significant value 0.05, so Ho is rejected or Ha is accepted. So, it can be concluded that there is an influence of the application of the Project Based Learning (PjBL) learning model on student learning outcomes in PPKn subjects. The test results of the average normalized gain (n-gain) of learning outcomes, the average score for increasing student learning outcomes calculated based on the normalized gain was obtained at 0.7761 with high criteria. Meanwhile, the test results for the average normalized gain (n-gain) percent of learning outcomes were obtained at 77.6067%, which shows the effective interpretation category. So, it can be concluded that the application of the Project Based Learning (PjBL) learning model to student learning outcomes in Civics subjects is effective.